The 4th IEEE International NanoElectronics Conference 2011
DOI: 10.1109/inec.2011.5991798
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching characteristics of zinc oxide (ZnO) resistive RAM with Al metal electrode

Abstract: This work investigates the characteristics of ZnO film as resistive RAM (RRAM) using Al electrode. Effects of oxygen composition in ZnO film is also studied using different Ar/O 2 gas flow ratio. From the electrical characteristics, the resistance ratio (HRS/LRS) can be up to 10 10 , and the set and reset voltage is lower to 0.5V and 2.5V, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Hence, unsatisfactory switching characteristics may be experienced due to the excess volume of native point defects. Numerous attempts have been reported in the literature on ZnO's switching dynamics based on electrodes' effects to alleviate ZnO's defects for improving switching characteristics, such as ZnO's stacking with various metal electrodes [120]- [124]. In RRAM, electrodes serve as the transport path for charge carriers and affect the resistance switching behaviour.…”
Section: Zno For Rram Application a Significance Of Electrodes In Zno Based Rrammentioning
confidence: 99%
“…Hence, unsatisfactory switching characteristics may be experienced due to the excess volume of native point defects. Numerous attempts have been reported in the literature on ZnO's switching dynamics based on electrodes' effects to alleviate ZnO's defects for improving switching characteristics, such as ZnO's stacking with various metal electrodes [120]- [124]. In RRAM, electrodes serve as the transport path for charge carriers and affect the resistance switching behaviour.…”
Section: Zno For Rram Application a Significance Of Electrodes In Zno Based Rrammentioning
confidence: 99%
“…Kim [8] Proved sol-gel-derived zinc oxide (ZnO) can also be used to manufacture resistors. Lin's first work [9] investigated the resistive switching characteristics of Al/ZnO/Al RRAM for ZnO film with and without N2 RTA treatment; He's second work [10] investigated the characteristics of ZnO film as resistive RAM (RRAM) using Al electrode. Zhao [11] explored the effect of electrode material to the properties of resistance.…”
Section: Theoretical Studies On Memristormentioning
confidence: 99%
“…It was found that RRAMs based on TaO x 26 and AlO x 27 require a high programming voltage, while those based on SiO 2 have inferior device stability due to the high ion mobility in SiO 2 , which leads to the dendritic growth of conductive filaments (CFs). 28 Additionally, ZnO- 29 and TiO 2 30 -based RRAMs have a high leakage current density thanks to the narrower bandgap of these metal oxides. It turns out that HfO 2 is one of the promising dielectric layers for RRAMs due to its excellent resistive switching (RS) characteristics such as a large resistive window, a low V set , and good endurance and retention characteristics.…”
Section: Introductionmentioning
confidence: 99%